Pengaruh Fokus Kerja Petugas Boarding Gate PT Gapura Angkasa terhadap Efektivitas Pelayanan Penumpang Maskapai Citilink di Yogyakarta International Airport - Fani, Silvi Indria; Ginusti, Gallis Nawang (Jurnal Ground Handling, 2025)
The difficulty of boarding gate officers in maintaining work focus has the potential to reduce the effectiveness of services to passengers during the boarding process. Therefore, this study aims to analyze the effect of the work focus of boarding gate officers on the effectiveness of Citilink Airline passenger services at Yogyakarta International Airport. This research uses quantitative methods with data collection through questionnaires. Involving all boarding gate officers of PT Gapura Angkasa at Yogyakarta International Airport, totaling 40 people. The data was then analyzed using simple linear regression method, T test, determination test (R2), and descriptive statistical test. The results of this study indicate that the results of simple linear regression indicate that the work focus of boarding gate officers affects the effectiveness of passenger services as evidenced by the results of the T test which shows a significance value of (0.000 <0.050). The magnitude of the influence of the work focus of boarding gate officers on the effectiveness of passenger service is 80% while the remaining 20% is influenced by other variables or factors not used in this study. The descriptive statistical test results show that the mean value of each indicator is at a high level with a low standard deviation, indicating a consistent officer work focus and contributing positively to the effectiveness of passenger service. In other words, it is concluded that increasing the work focus of boarding gate officers is very influential in increasing the effectiveness of passenger services in the boarding area.